2019
DOI: 10.18510/hssr.2019.741
|View full text |Cite
|
Sign up to set email alerts
|

Vietnam's Electronics Industry: The Rise and Problems of Further Development

Abstract: Purpose: To evaluate the Vietnamese electronics industry (EI) by analyzing its successes and shortcomings in recent years in comparison with other Southeast Asian countries, as well as the problems faced by the young industries in Vietnam in the course of its development and identify their abilities to participate in the global value chain. Methodology: Systems approach was used to analyze the status of Vietnam’s EI. The advantages and the results achieved by EI are assessed and described with the help o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Studying the status of domestic enterprises, it can be concluded that the above weakness are the barriers that prevent domestic suppliers from participating deeply in the supply chains and getting expected value added. Moreover, domestic enterprises weakness even increases the import dependence and it is easily exploited by foreign investors to adopt a transfer pricing system to avoid paying taxes and achieving high profits by raising the price of imported equipment's, technology, raw materials produced by their overseas companies located in other countries [13]. In order to solve the problems, it is necessary to take comprehensive measures addressing creating domestic suppliers' power and balancing supplier-buyer relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Studying the status of domestic enterprises, it can be concluded that the above weakness are the barriers that prevent domestic suppliers from participating deeply in the supply chains and getting expected value added. Moreover, domestic enterprises weakness even increases the import dependence and it is easily exploited by foreign investors to adopt a transfer pricing system to avoid paying taxes and achieving high profits by raising the price of imported equipment's, technology, raw materials produced by their overseas companies located in other countries [13]. In order to solve the problems, it is necessary to take comprehensive measures addressing creating domestic suppliers' power and balancing supplier-buyer relationship.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, export production efficiency is low because: (i) most enterprises involved in export processing, including both domestic enterprises and FIEs, are capital and labor intensive and inclined toward outsourcing and assembling final products; (ii) the supporting industry is underdeveloped, resulting in very few domestic suppliers; and (iii) the "transfer pricing" tactics of transnational companies to reduce tax payable to gain high profits by increasing the price of equipment, technology, and raw materials imported from their subsidiaries [53,52]. Thus, the direct contribution of exports to GDP is still very modest, and this does not contradict similar conclusions in the study of Sahoo & Kumar [54].…”
Section: Discussionmentioning
confidence: 99%
“…Knes (Knes, 2010), Ngoc & Binh (Ngoc & Binh, 2019), Raj-Reichert (Raj-Reichert, 2020), Hou (Hou, 2020), and Yaghmaie (Yaghmaie et al, 2020) have thoroughly observed the production of advanced equipment and hardware. Balkenende & Bakker (Balkenende & Bakker, 2015), Helo (Helo et al, 2009), and Yun & Lee (Yun & Lee, 2022) have stressed the issues of corporate governance and sustainability.…”
Section: Methodsmentioning
confidence: 99%